Transformation and development : the political economy of transition in India and China - Bagchi, Amiya Kumar; D'Costa, Anthony P., 1957- (New Delhi : Oxford University Press, 2013)
In twelve incisive essays covering a wide range of issues, this volume undertakes an interdisciplinary and multi-level analysis and provides comprehensive and critical insights into the dynamics of the development process in these two countries.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Economic development -- China; Economic development -- India; China -- Economic conditions -- 2000-; India -- Economic conditions -- 1991-